Clinical and economic impact of HeartLogic™ compared with standard care in heart failure patients. (22nd February 2021) - Treskes, Roderick W.; Beles, Monika; Caputo, Maria‐Luce; Cordon, Audrey; Biundo, Eliana; Maes, Edith; Egorova, Anastasia D.; Schalij, Martin J.; Van Bockstal, Koen; Grazioli‐Gauthier, Lorenzo; Vanderheyden, Marc; Bartunek, Jozef; et al.
Abstract: Aims: The implantable cardiac defibrillator/cardiac resynchronization therapy with defibrillator‐based HeartLogic™ algorithm has recently been developed for early detection of impending decompensation in heart failure (HF) patients; but whether this novel algorithm can reduce HF hospitalizations has not been evaluated. We investigated if activation of the HeartLogic algorithm reduces the number of hospital admissions for decompensated HF in a 1 year post‐activation period as compared with a 1 year pre‐activation period. Methods and results: Heart failure patients with an implantable cardiac defibrillator/cardiac resynchronization therapy with defibrillator with the ability to activate HeartLogic and willingness to have remote device monitoring were included in this multicentre non‐blinded single‐arm trial with historical comparison. After a HeartLogic alert, the presence of HF symptoms and signs was evaluated. If there were two or more symptoms and signs apart from the HeartLogic alert, lifestyle advices were given and/or medication was adjusted. After activation of the algorithm, patients were followed for 1 year. HF events occurring in the 1 year prior to activation and in the 1 year after activation were compared. Of the 74 eligible patients (67.2 ± 10.3 years, 84% male), 68 patients completed the 1 year follow‐up period. The total number of HF hospitalizations reduced from 27 in the pre‐activation period to 7 in the post‐activation period ( P = 0.003). The number of patients hospitalized for HF declined from 21 to 7 ( P = 0.005), and the hospitalization length of stay diminished from average 16 to 7 days ( P = 0.079). Subgroup analysis showed similar results ( P = 0.888) for patients receiving cardiac resynchronization therapy during the pre‐activation period or not receiving cardiac resynchronization therapy, meaning that the effect of hospitalizations cannot solely be attributed to reverse remodelling. Subanalysis of a single‐centre Belgian subpopulation showed important reductions in overall health economic costs ( P = 0.025). Conclusion: Activation of the HeartLogic algorithm enables remote monitoring of HF patients, coincides with a significant reduction in hospitalizations for decompensated HF, and results in health economic benefits.